Corporate cosmos: How commercial American space imagines our future and shapes our present - Vibeke Schou Tjalve (Danish Institute for International Studies (DIIS), 2024)
Over the past ten years, and without a lot of public or political attention, space has become a site of commercial investment and development. Already much in our daily lives depends on growing satellite systems, crowding Earth's orbit, for communication, navigation, weather information, and the surveillance and prediction of climate change patterns. And in just a few years ambitious plans for industrial development in outer space will, too, be on the threshold of fruition: helium and mineral mining, water extraction, solar engineering, and permanent base building. We have entered the age of the orbital economy and the rise of commercial space actors. This report explores the ideas and ambitions of what is currently the most dominant force within that new landscape: the American space industry, which is effectively an extension of American tech, and as such wields unparalleled forms of private power. More specifically, the report unpacks an American space industry driven not just by profit, but by two grand-scale visions of the future. Firstly, a tech-optimist vision of space as a climate solution: a both profitable and sustainable way out of contemporary ecological dilemmas. Secondly, a tech-libertarian vision of space as a place of political revolution: a realm free from the reach of states, and as such an arena in which the virtues of market innovation might be displayed. [...]
Keywords: 300; space; USA; security; geopolitics; tech; space industry